Ghosts of the past: how drought legacy effects shape forest functioning and carbon cycling. (10th March 2020) - Kannenberg, Steven A.; Schwalm, Christopher R.; Anderegg, William R. L.
Abstract: Multi‐year lags in tree drought recovery, termed 'drought legacy effects', are important for understanding the impacts of drought on forest ecosystems, including carbon (C) cycle feedbacks to climate change. Despite the ubiquity of lags in drought recovery, large uncertainties remain regarding the mechanistic basis of legacy effects and their importance for the C cycle. In this review, we identify the approaches used to study legacy effects, from tree rings to whole forests. We then discuss key knowledge gaps pertaining to the causes of legacy effects, and how the various mechanisms that may contribute these lags in drought recovery could have contrasting implications for the C cycle. Furthermore, we conduct a novel data synthesis and find that legacy effects differ drastically in both size and length across the US depending on if they are identified in tree rings versus gross primary productivity. Finally, we highlight promising approaches for future research to improve our capacity to model legacy effects and predict their impact on forest health. We emphasise that a holistic view of legacy effects – from tissues to whole forests – will advance our understanding of legacy effects and stimulate efforts to investigate drought recovery via experimental, observational and modelling approaches. Abstract : This review synthesizes current research on legacy effects, reviews the evidence behind hypothesized mechanisms for drought legacies, and discusses key knowledge gaps pertaining to how they impact the carbon cycle. Additionally, through a novel data synthesis this study demonstrates that lags in drought recovery are much more severe when quantified in tree rings versus gross primary productivity.